Edukasi etika dan pemanfaatan artificial intelligence secara bijak bagi peserta didik sekolah dasar - Atmaja, Niko Surya; Harahap, Sahyunan (Nur Science Institute, 2026)
The use of digital devices supported by artificial intelligence has become increasingly common in elementary school learning activities; however, it is not always accompanied by adequate ethical understanding. This condition may lead to issues with academic honesty, critical thinking, and responsible use of technology. This community service activity aimed to provide elementary school students at Yayasan Pendidikan Islam Al-Fakhri with education on the ethical and responsible use of artificial intelligence. A participatory approach was employed, involving students and teachers at the stages of needs identification, program planning, educational implementation, simulations, mentoring, and evaluation. The activities focused on introducing basic artificial intelligence concepts, ethical principles in technology use, and responsible learning practices. Data were collected through direct observation, reflective discussions, and students’ responses during the activities. The results indicate increased awareness of ethical use of technology, improved understanding of academic honesty, and enhanced ability to evaluate digital information critically. Students began to perceive artificial intelligence as a learning support tool rather than a substitute for independent thinking.